The Utilization of the Sido Ing Rejek Tomb As a Resource for Local History in South Sumatra - Dicky Jhonson Saputra; Dedi Irwanto (Tarikhuna: Journal of History and History Education, 2025)
This study examines the historical and educational significance of the Sido Ing Rejek Tomb in Sakatiga, Ogan Ilir, primarily addressing the lacuna in academic research and public awareness regarding its potential as a local historical resource. The research employed a library-based methodology, focusing on the synthesis and critical analysis of pertinent secondary literature (historical texts, journals, and local records) to reconstruct the role of royal cemeteries in Palembang historiography and their application in education. Findings reveal the Tomb's dual role as a material and symbolic heritage. Materially, it provides tangible evidence for historical and archaeological analysis; symbolically, it embodies the legacy of anti-colonial resistance, collective memory, and cultural identity in South Sumatra. The analysis underscores the significance of oral traditions, ritual practices, and community narratives in ensuring the Tomb's generational salience. This approach contributes to historical discourse by integrating local perspectives often marginalized by dominant narratives, while also illustrating the site's capacity for historical education and character development. The research is limited by its reliance on secondary sources, specifically the absence of direct field research or archaeological validation; consequently, the empirical veracity of the analysis is preliminary. This constraint, however, creates ample opportunities for future interdisciplinary research engaging historians, archaeologists, anthropologists, and local communities. In conclusion, the Sido Ing Rejek Tomb should be conserved and developed not merely as a historical site but as a crucial vehicle for historical education and sustainable cultural tourism, making it an invaluable asset for reinforcing academic inquiry and national identity.